MySQL/PHP Database Applications - Greenspan, Jay (IDG Books Worldwide, 2011)
More businesses and ambitious individuals are trying to bring applications to the Web but they are bewildered with the array of components and concepts needed to create a data-driven site. The cost, stability and ease of development using the Open Source PHP 4 scripting language and a MySQL database makes this combination the best choice for small and mid-size Web-based applications. PHP4/MySQL Database Applications demonstrates web-application development by presenting seven real, ready-to-use examples starting with a simple guess book and ending with a fully-functional e-commerce site with a shopping cart. Inexperienced users will learn the essentials of working with PHP4 and MySQL so they can start building and customizing database applications for the web right away!